2012
DOI: 10.1890/es12-00299.1
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and taxonomic biases in research on biodiversity in human‐modified landscapes

Abstract: Abstract. Biodiversity persistence in human-modified landscapes is crucial for conservation and maintaining ecosystem services. Studies of biodiversity in landscapes where humans live, work, and extract resources could support defensible policy-making to manage land-use. Yet, research should cover relevant regions, and biases in study topics should not lead to gaps in the evidence base. We systematically reviewed the literature of biogeography in human-modified landscapes published in eight eminent biogeograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 58 publications
5
64
0
1
Order By: Relevance
“…The geographical and ecosystem distributions we observed are consistent with other similar assessments [31,32]. Other than the compelling evidence of the attraction of insects to artificial structures, only three studies have demonstrated a trap in freshwater ecosystems, and none in marine environments.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The geographical and ecosystem distributions we observed are consistent with other similar assessments [31,32]. Other than the compelling evidence of the attraction of insects to artificial structures, only three studies have demonstrated a trap in freshwater ecosystems, and none in marine environments.…”
Section: Resultssupporting
confidence: 90%
“…While conservation research in human modified landscapes is likely to be most important in areas where human pressure is greatest, these areas are also the least studied [32]. There has been much interest in understanding the biodiversity impacts of land-use change in the tropics (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…On the bright side, scientific interest in the topic is increasing (Trimble and van Aarde 2012), and as research accumulates, it will allow for systematic reviews useful for policy decisions. Additionally, many issues associated with human-wildlife coexistence are primarily 33 related to large mammals and efforts to solve these problems should continue.…”
Section: Resultsmentioning
confidence: 99%
“…1), particularly rich in biodiversity. Research on biodiversity in human-modified landscapes is biased towards tropical forests (Trimble and van Aarde 2012). Nonetheless, biodiversity in human-modified tropical forest landscapes in Africa has received much less scientific attention than in other regions, especially South and Central America (Gardner et al 2010).…”
Section: Tropical Forestsmentioning
confidence: 99%
See 1 more Smart Citation